PENGEMBANGAN BAHAN AJAR BANGUN DATAR BERBASIS KEARIFAN LOKAL SUKU AMANUBAN SELATAN UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS III - Darni Regisarmi Neken; Yulsy Marselina Nitte; Radka Bodkova Koli (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
Local wisdom-based teaching materials play an important role in creating contextual and meaningful learning experiences. This study aimed to develop South Amanuban local wisdom-based teaching materials on plane figures and to determine their feasibility, practicality, and effectiveness in improving the learning outcomes of third-grade students at SD Negeri Oelbubuk. The study employed a Research and Development (R&D) method using the ADDIE model, which consists of Analyze, Design, Development, Implementation, and Evaluation stages. The research subjects were 20 third-grade students of SD Negeri Oelbubuk. The research instruments included expert validation sheets, teacher and student response questionnaires, and learning outcome tests. Data were analyzed using descriptive quantitative analysis and the N-Gain test. The results showed that the developed teaching materials were categorized as highly feasible based on assessments from material, language, and media experts. Teacher and student responses indicated that the teaching materials were practical to use in the learning process. Furthermore, students’ learning outcomes improved after the implementation of the teaching materials, as reflected by the increase from pre-test to post-test scores, with an N-Gain score of 0.5774 categorized as moderate. Therefore, the South Amanuban local wisdom-based teaching materials were found to be feasible, practical, and effective in improving elementary school students’ mathematics learning outcomes on the topic of plane figures. ABSTRAK Bahan ajar berbasis kearifan lokal memiliki peran penting dalam menciptakan pembelajaran yang kontekstual dan bermakna. Penelitian ini bertujuan untuk mengembangkan bahan ajar berbasis kearifan lokal Suku Amanuban Selatan pada materi bangun datar serta mengetahui tingkat kelayakan, kepraktisan, dan keefektifannya dalam meningkatkan hasil belajar siswa kelas III SD Negeri Oelbubuk. Penelitian ini menggunakan metode Research and Development (R&D) dengan model pengembangan ADDIE yang meliputi tahap Analyze, Design, Development, Implementation, dan Evaluation. Subjek penelitian terdiri atas 20 siswa kelas III SD Negeri Oelbubuk. Instrumen penelitian meliputi lembar validasi ahli, angket respons guru dan siswa, serta tes hasil belajar. Data dianalisis menggunakan teknik analisis deskriptif kuantitatif dan uji N-Gain. Hasil penelitian menunjukkan bahwa bahan ajar yang dikembangkan memperoleh kategori sangat layak berdasarkan penilaian ahli materi, ahli bahasa, dan ahli media. Respons guru dan siswa menunjukkan bahwa bahan ajar praktis digunakan dalam pembelajaran. Selain itu, hasil belajar siswa mengalami peningkatan setelah penggunaan bahan ajar yang ditunjukkan oleh kenaikan nilai rata-rata dari pretest ke posttest dengan nilai N-Gain sebesar 0,5774 yang termasuk kategori sedang. Dengan demikian, bahan ajar berbasis kearifan lokal Suku Amanuban Selatan dinyatakan layak, praktis, dan efektif digunakan untuk meningkatkan hasil belajar matematika siswa sekolah dasar pada materi bangun datar.